Home improvement, wealth inequality, and the energy-efficiency paradox - Martijn I. Dröes; Yasmine van der Straten (Tinbergen Institute, 2024)
This article examines the rate at which different households go green and how this affects the distribution of both wealth and CO2 benefits. Using a unique dataset from the Netherlands, we find that lower-income households are less likely to make their homes more energy efficient. At the same time, higher-income households sort themselves into homes that are already more energy efficient to begin with. Over a 15-year horizon, the combined effect on energy savings accumulates to 17% of median net wealth, with ex ante sorting explaining 65% of this effect. Although a policy that encourages lower-income households to own energy-efficient homes reduces wealth inequality and poverty, it leaves 83% of the potential CO2 benefits unrealized because the brownest households are in the upper part of the income distribution. Our results indicate that there is a policy trade-off between sheltering low-income households against climate risk on the one hand and effectively reducing CO2 emissions on the other.
Keywords: D31; Q41; Q43; Q54; R31; 330; Energy efficiency; home improvement; wealth inequality; CO2 emissions